2021
DOI: 10.1128/spectrum.01103-21
|View full text |Cite
|
Sign up to set email alerts
|

Direct Rapid Identification from Positive Blood Cultures by MALDI-TOF MS: Specific Focus on Turnaround Times

Abstract: Using MALDI-TOF MS directly from blood culture bottles reduces the time required for pathogen identification, and the turnaround times for final identification have been compared with overnight incubation from solid media in previous studies. However, identification from a short incubation of agar plates has been increasingly accepted and successfully implemented in routine laboratories, but there is no data comparing direct MALDI-TOF MS with the short-term, incubated agar plates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, BCs in daily practice usually requires a time of positivity that commonly exceed 10 h, sometimes even more. Recent technical advances allow to perform identification directly on positive BCs bottles without needing to subculture the medium on agar plate with as good analytical performances as the standard practice [ 30 , 31 ]. As a result, turnaround times are drastically reduced to a ‘within a day period’ with a rapid identification protocol [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BCs in daily practice usually requires a time of positivity that commonly exceed 10 h, sometimes even more. Recent technical advances allow to perform identification directly on positive BCs bottles without needing to subculture the medium on agar plate with as good analytical performances as the standard practice [ 30 , 31 ]. As a result, turnaround times are drastically reduced to a ‘within a day period’ with a rapid identification protocol [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent technical advances allow to perform identification directly on positive BCs bottles without needing to subculture the medium on agar plate with as good analytical performances as the standard practice [ 30 , 31 ]. As a result, turnaround times are drastically reduced to a ‘within a day period’ with a rapid identification protocol [ 31 ]. Still, this kind of protocol is not available in routine practice and so there is a loss of chance between daytime and night-time positive samples.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional culture and blood culture bottle culture are often used in clinical laboratories. A previous study showed that the mean detection times for routine microbial culture and blood culture combined with MALDI-TOF MS for suspected endophthalmitis are 5.39 ± 0.56 days and 3.17 ± 0.40 days, respectively ( 14 ). To shorten the incubation time, we used micro-LB broth for incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria inactivated by antibiotics cannot proliferate on the plate, and it is difficult to identify them by MALDI-TOF-MS alone ( 17 ). Finally, the MALDI-TOF-MS assay is not suitable for aqueous samples with low bacterial load, which may be the early stage of endophthalmitis ( 10 , 14 , 16 , 17 ). Therefore, we need to combine special sample preparation protocols with mass spectrometry to overcome these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, by using differential centrifugation isolation procedure, urine tract pathogens have been identified at species level with high confidence from urine specimens either directly (159/211 cases, 74.5% accuracy) or after a short‐term culture (182/211 cases, 84.9% accuracy) 65 . Enrichment procedures like immune‐affinity combined with magnetic separation, 34 centrifugation in serum separator tubes, 66 and acoustic trapping with enrichment microchip 67 allowed direct bacterial identification at species level from positive blood cultures or short‐term blood cultures in only 1–4 h of turnaround time with high accuracy (e.g., 289/295 cases, 97.9% accuracy). Bacterial mixtures have also been successfully identified at species level, without bacterial strain purification via strategies like single colony plating, by using a novel algorithm framework containing synthetic mixture modeling, similarity scoring, and Jackknife modeling (Figure 2A).…”
Section: Applications In Rapid Precise Diagnosticsmentioning
confidence: 99%